2020
DOI: 10.1371/journal.pone.0231752
|View full text |Cite
|
Sign up to set email alerts
|

Retinal astrocytes transcriptome reveals Cyp1b1 regulates the expression of genes involved in cell adhesion and migration

Abstract: Astrocytes (AC) are the most abundant cells in the central nervous system. In the retina, astrocytes play important roles in the development and integrity of the retinal neurovasculature. Astrocytes dysfunction contributes to pathogenesis of a variety of neurovascular diseases including diabetic retinopathy. Recent studies have demonstrated the expression of Cyp1b1 in the neurovascular cells of the central nervous system including AC. We recently showed retinal AC constitutively express Cyp1b1, and global Cyp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…In normal and tumor cells, mitotic nuclear division, cell cycle, and meiotic division of oocytes are known to be important cellular processes, 28 and key tumor-related genes usually modulate tumor progression by regulating these cellular processes. 29 Furthermore, some studies have shown that cell adhesion molecules play crucial roles in tumor development, 30 consistent with our current results. Thus, although the specific mechanisms of disease progression are still not clearly defined, the signaling pathways identified above were confirmed to be related to NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…In normal and tumor cells, mitotic nuclear division, cell cycle, and meiotic division of oocytes are known to be important cellular processes, 28 and key tumor-related genes usually modulate tumor progression by regulating these cellular processes. 29 Furthermore, some studies have shown that cell adhesion molecules play crucial roles in tumor development, 30 consistent with our current results. Thus, although the specific mechanisms of disease progression are still not clearly defined, the signaling pathways identified above were confirmed to be related to NSCLC.…”
Section: Discussionsupporting
confidence: 92%
“…1,26 Our hypothesis could therefore be that given SNPs in CYP1B1 gene may modify the synthesis of Cyp1b1 enzyme, which is crucial in reactions involved in drug metabolism and synthesis of cholesterol, steroids and other lipids. 10,34,35 It had been reported that a decreased activity of the Cyp1b1 enzyme could be associated with an increment of the oxidative stress 36 affecting the protein stability or corrupting collagen disposition in some body tissues like trabecular meshwork's. 8 In addition, CYP1B1 gene SNP also could modify metabolism of the retinol, stradiol and other complex molecules such as polycyclic aromatic hydrocarbons metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion signaling pathway was important for maintaining the integrity of retinal vascular structure and function [51,52]. According to the study results, those genes enriched in focal adhesion signaling pathway were considerably upregulated [53][54][55]. Moreover, proteomic bioinformatic analysis in DR indicated that DR development was closely related to focal adhesion and PI3K-Akt signaling pathway [56].…”
Section: Discussionmentioning
confidence: 99%